Testimoni Penggunaan Hukum Islam dalam Naskah Serat Ambiyo Pelemgadung Sragen (1907M) - Ahmad Wahyu Sudrajad (Perpustakaan Nasional RI, 2022)
Islamic law has been attached to the customs of the Javanese people and has a function as the norm of community life. This Islamic law runs in harmony without having to negate the existing culture. The arrival of the Dutch colonials to the archipelago resulted in changes in the political and social system. The laws and regulations were domesticated by the Dutch colonials and only applied to indigenous peoples. These rules do not necessarily make people leave the law based on Islamic teachings. In this manuscript of Serat Ambiyo Pelemgadung there is an agreement regarding the chapter on leasing based on Islamic law. This chapter is one of the important evidences that Islamic law is still used in society, in addition to the rules made by the Dutch. For more detail in analyzing the chapter, the researcher uses the Testimony analysis from Shoshana Felman. Felman’s study is indeed suitable in this study, especially Islamic law at that time was experiencing repression from the colonial government. The notes in this manuscript are important to be studied as evidence of testimony that Islamic law is still used in Javanese society.